Da exclusão do campo à inclusão na prisão: a gestão penal da pobreza agrária no Brasil - Oliveira, Nayana Guimarães Souza de (2017)
This research aims to be a study about the criminal management of agrarian poverty in the temporal space that goes from the urban and industrial transformation of Brazil to the present. It seeks to unravel the socially excluding and criminally inclusive impacts of the rapid urbanization and industrialization process in Brazil. The emptying of the countryside that happened in the same time with the expansion of the cities, was one of the causes of structural unemployment and the formation of the urban peripheries, where the marginalized majority of the population is segregated. To cross this path, the genesis of the periphery is studied, building a bridge between the exclusion of the countryside and urban segregation. It takes care of delineating the Brazilian land characteristics, a context in which the rural-urban migratory movement and the process of rural and urban poverty formation are inserted. It stands out as the State - in which hopes of realizing socially guaranteed rights are placed - has become increasingly a minimal State, with minimum obligations. In sequence, this study deals with the criminal management of poverty in Brazil through the expansion of repression directed at poor individuals, with a stratospheric increase in public expenditures directed at the expansion of a police force that, however, isn’t succeed in effectively combating the increase of urban violence, since this is part of the contradictions proper to capitalism. In this society created by the contradictions of the economic system, the poor, the “favelado” and marginalized, is easy target of the police apparatus of the State, while it does not guarantee social rights; He is seen as dangerous individual and inspires distrust for the most privileged classes in society. In this Penal State, not only the repressive apparatus of the State grows, but also private security; on the other had, the rate of incarceration increases, especially of the poorer class of the population. Thus, there is an interweaving between agrarian question, criminal issue and urban violence, which involves the transfer of agrarian poverty to the cities, the formation of urban peripheries and the segregation of the poor’s in this places, where they will receive very little of the rule of law and will perceive the daily presence of the Criminal State.